Strategy to Increase the Efficiency of Sharia Banks - Muhammad Fathi; Muhammad Taqy Shandyka (Ekonomi Islam Indonesia, 2025)
Efficiency is one of the main challenges faced by the Islamic banking industry in Indonesia, especially in the face of competitive pressures, limited business scale, and performance sustainability demands. This study aims to identify and prioritize strategies to improve the efficiency of Islamic banks in Indonesia based on the views of experts. The method used is the Delphi method involving nine expert respondents consisting of academics, practitioners, and Islamic banking regulators. The analysis was carried out using statistical indicators in the form of mean values, standard deviations, and interquartile range (IR) to measure the consensus level. The results of the study showed that of the twelve variables of the strategy to improve the efficiency of Islamic banks, ten variables reached a consensus, while two variables were declared non-convergent. The three main strategies prioritized by experts are increasing revenue, optimizing branch office networks, and increasing organizational effectiveness. These findings provide strategic implications for Islamic bank management and regulators in formulating more targeted and sustainable efficiency improvement policies.